Microwave-assisted intralesional curettage combined with other adjuvant methods for treatment of Campanacci III giant cell tumor of bone in distal radius: a multicenter clinical study - Cui, Haocheng; Li, Jianhua; Zheng, Kai; Xu, Ming; Zhang, Guochuan; Hu, Yongcheng; Yu, Xiuchun (Frontiers in Oncology, 2024)
Objective To compare the clinical outcomes of microwave-assisted intralesional curettage(MAIC) with those of en bloc resection and autogenous fibular reconstruction (EBR-AFR) for treating grade III giant cell tumor of the bone (GCTB) of the distal radius and to elucidate the indications for wrist preservation surgery.In this retrospective study, 19 patients with grade III GCTB of the distal radius who underwent surgery at three medical institutions were included and categorized based on their surgical pattern. Seven patients underwent MAIC and internal fixation with bone cement (MAIC group) and 12 underwent EBR-AFR (EBR-AFR group). To evaluate the function of the affected limb postoperatively, wrist range of motion, grip strength, Musculoskeletal Tumor Society (MSTS) scores were recorded.The follow-up time of the MAIC group was 73.57 ± 28.61 (36-116) months, with no recurrence or lung metastasis. In contrast, the follow-up time of the EBR-AFR group was 55.67 ± 28.74 (36-132) months, with 1 case of local recurrence (8.3%, 1/12) and 1 case of lung metastasis (8.3%, 1/12). The wrist flexion, extension, supination, pronation, grip strength were better in the MAIC group than in the EBR-AFR group. Although there was no statistically significant difference in the MSTS score between the two groups, it is noteworthy that the MAIC group exhibited significantly superior emotional acceptance and hand positioning compared to the EBR-AFR group(p < 0.05).The functional outcomes of the MAIC group are better. The treatment strategy for grade III GCTB of the distal radius should be determined based on the specific preoperative imaging findings. Nevertheless, MAIC can be the preferred surgical approach for most patients with grade III GCTB of the distal radius, particularly for young patients.